Determinants of Burnout Among Healthcare Professionals Working in the Labour Room of a Tertiary Care Hospital in South Punjab, Pakistan - Zahoor, Sadia; Zahoor, Mamoona; Javed, Faiza; Najam, Mahwish; Aslam, Shahida; Yasmeen, Iffat (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find out the frequency and determinants of burnout among healthcare workers and staff working in a labour room of a Gynaecology unit of a tertiary care hospital in South Punjab, Pakistan.Study Design: Cross-sectional study.Place and Duration of the Study: Department of Obstetrics and Gynaecology, Shaikh Zayed Hospital, Rahim Yar Khan, Pakistan, from Mar to May 2022.Methodology: A total of 93 healthcare workers, including doctors and nurses from the labour room of the study centre, were included. Possible causes of burnout were noted. The 16-item instrument OLBI was utilized.Results: Of the 93 study participants, 35(37.6%) were post-graduate residents. High exhaustion was reported by 61(65.6%) study participants, while high disengagement was noted in 44(47.3%). Burnout was reported by 38(40.9%) study participants. Age (p=0.006), marital status as married (p=0.004), designation as post-graduate resident (p